Value of Platelet Indices in Diagnosing Etiology of Thrombocytopenia (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background:Platelet parameters are significant, especially in diagnosis of causes of thrombocytopenia. The platelet parameters are widely available as part of full blood count with no extra cost. Thrombocytopenia is of varying etiology, it is broadly divided into three major categories (1) as increased destruction (ITP), (2) decreased production and (3) splenic sequestration/abnormal pooling.Aims of the study: To investigate the  indices of  the platelets which include( MPV,PDW,PCT) and to signify its role in the diagnosing the etiology of thrombocytopenia,, if there is any correlation between platelet count and platelets indices and to determine cut off point of MPV for the diagnosis of ITP.                                Materials and Methods: 104 cases of Thrombocytopenia (TCP) and 50control cases having normal platelet count were selected. TCP was defined as platelet count